Homecoming queers : desire and difference in Chicana Latina cultural production - Danielson, Marivel T. (Rutgers University Press, 2009)
Homecoming Queers provides a critical discussion of the multiple strategies used by queer Latina authors and artists in the United States to challenge silence and invisibility within mainstream media, literary canons, and theater spaces. Marivel T. Danielson's analysis reveals the extensive legacy of these cultural artists, including novelists, filmmakers, students and activists, comedians, performers, and playwrights. By clearly discussing the complexities and universalities of ethnic, racial, sexual, gender, and class intersections between queer Chicana and U.S. Latinas, Danielson ex.
Keywords: American literature -- Hispanic American authors -- History and criticism.; American literature -- Women authors -- History and criticism.; Lesbians' writings, American -- History and criticism.; Home in literature.; Hispanic Americans in the performing arts.; Hispanic American lesbians -- Intellectual life.; Space in literature.; Languages & Literatures.; American Literature.; English.; Littérature américaine -- Auteurs américains d'origine latino-américaine -- Histoire et critique.; Écrits de femmes américains -- Histoire et critique.; Écrits de lesbiennes américains -- Histoire et critique.; Foyer dans la littérature.; Américains d'origine latino-américaine dans les arts du spectacle.; Lesbiennes américaines d'origine latino-américaine -- Vie intellectuelle.; Espace dans la littérature.; ART -- Reference.; ART -- Performance.; SOCIAL SCIENCE -- Gay Studies.; Lesbianismo -- En la literatura; Literatura hispanoamericana -- Autoras -- Historia y crítica; American literature -- Hispanic American authors; American literature -- Women authors; Hispanic Americans in the performing arts; Home in literature; Lesbians' writings, American; Space in literature; Lesbe; Autorin; Littérature américaine -- Auteurs d'origine latino-américaine -- Histoire et critique.; Littérature hispano-américaine -- Femmes écrivains -- Thèmes, motifs.; Écrits de lesbiennes américaines -- Thèmes, motifs.; Foyer -- Dans la littérature.; Américains d'origine latino-américaine -- Et les arts du spectacle.; Hispanos.; Criticism, interpretation, etc.